Caracterización teológica de la cosmología de Platón en la apologética de Atenágoras de Atenas (2021)
Some elements of the Platonic philosophy established in apologetic treatises of many Christian writers among which are athenian Atenágoras and his well-known work πρεσβεία περὶ χριστιανῶν, whose version of the spanish Hellenist and theologian Daniel Ruiz will be the object of study in this text, demonstrate a special interest in the exposition of cosmology. Although this theme serves as an attempt to rationally demonstrate the transcendence of the divine and the subsequent generation of the universe because of God's design and power, it is not a meticulous exposition of the ideas of philosophers that Athenagoras himself cites but rather of a Christian exegesis about Plato’s cosmology in which it seems that such writers incurred, to make a deep reflection on faith.